Akulmiut neqait: fish and food of the Akulmiut - Fienup-Riordan, Ann, author; Meade, Marie, author; Rearden, Alice, author; University of Alaska Press, publisher (Colorado State University. Libraries, 2019)
In fall 2014, Calista Education and Culture, Inc. (CEC, formerly Calista Elders Council) began a four-year study funded by the Office of Subsistence Management of the US Fish and Wildlife Service. The study focused on whitefish and other non-salmon freshwater fish harvested by residents of the Akulmiut villages of Kasigluk, Nunapitchuk, and Atmautluak, as well as those living along the Kuskokwim River just below Bethel in the villages of Napaskiak, Napakiak, and Oscarville. Harvest studies have been carried out in some of these communities (Ikuta, Brown, and Koester, ed. 2014) as well as two major ethnographic studies--one in Napaskiak (Oswalt 1963) and one in Nunapitchuk (Andrews 1989). Our intended focus was not on harvest amounts but rather traditional knowledge surrounding the harvest and use of the six species of whitefish, as well as pike, burbot, and blackfish, on which people from this area relied so heavily in the past and continue to harvest to this day. In fact, all three contemporary Akulmiut villages, as well as settlements in the past, were established at sites where fish fences were built across the river each fall to intercept whitefish as they migrated out of the lakes and sloughs toward the mainstem of the Kuskokwim River. If there is one food that defines people from this area, it is whitefish.--Provided by publisher.
Fish and food of the Akulmiut
Fish throughout the year -- Knowing the land and wilderness -- Care of fish and food -- All things have awareness -- Our world and weather are changing -- Yup'ik transcription and translation -- THINGS WE TALKED ABOUT. Food and family -- Fish throughout the year -- Hunting and fur trapping -- Food shortage -- Taking care of fish and food -- All things have awareness.
Keywords: Yupik Eskimos -- Alaska -- Yukon-Kuskokwim Delta -- Social life and customs; Yupik Eskimos -- Food -- Alaska -- Yukon-Kuskokwim Delta; Yupik Eskimos -- Fishing; Subsistence fishing -- Alaska, Southwest; Traditional ecological knowledge -- Alaska, Southwest; Whitefish fisheries -- Alaska, Southwest; Yukon-Kuskokwim Delta (Alaska) -- Social life and customs; Ethnology -- Alaska -- Yukon-Kuskokwim Delta Region; Older Yupik Eskimos -- Interviews; Central Yupik language -- Texts